In-plane anisotropic properties of 1T′-MoS2 layers - Nam, Gwang-Hyeon (2021)
Crystal phases play a key role in determining the physicochemical properties of a material. To date, many phases of transition metal dichalcogenides have been discovered, such as octahedral (1T), distorted octahedral (1T′), and trigonal prismatic (2H) phases. Among these, the 1T′ phase offers unique properties and advantages in various applications. Moreover, the 1T′ phase consists of unique zigzag chains of the transition metals, giving rise to interesting in-plane anisotropic properties. Herein, the in-plane optical and electrical anisotropies of metastable 1T′-MoS2 layers are investigated by the angle-resolved Raman spectroscopy and electrical measurements, respectively. The deconvolution of J1 and J2 peaks in the angle-resolved Raman spectra is a key characteristic of high-quality 1T′-MoS2 crystal. Moreover, it is found that its electrocatalytic performance may be affected by the crystal orientation of anisotropic material due to the anisotropic charge transport.